2018
DOI: 10.3390/nano8050281
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Magnetic Properties of Ni-Doped Zinc-Blende ZnO: A First-Principles Study

Abstract: The electronic structure, band structure, density of state, and magnetic properties of Ni-doped zinc-blende (ZB) ZnO are studied by using the first-principles method based on the spin-polarized density-functional theory. The calculated results show that Ni atoms can induce a stable ferromagnetic (FM) ground state in Ni-doped ZB ZnO. The magnetic moments mainly originate from the unpaired Ni 3d orbitals, and the O 2p orbitals contribute a little to the magnetic moments. The magnetic moment of a supercell includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Later, RTFM was also observed by Zhao et al 138 in Ni-, 2.25 atom %, doped ZnO thin film deposited by magnetron co-sputtering on a quartz substrate having the highest saturation magnetization of 0.055 μ B /Ni. However, an experimentally observed magnetic moment of Ni-doped ZnO was very less than the theoretical value calculated by Xue et al 139 which shows a magnetic moment of 0.79 μ B for a supper cell, which contains 32 Zn and 32 O atoms and containing a single Ni atom. In another work, He et al 140 found that electrical conductivity of ZnO increased 30 times on Ni doping, a higher oxidation state than Zn 2+ , with a decrease in resistivity from 390 to 12 ohm cm which is attributed to the Ni 3+ oxidation state which contributes to the hole carrier.…”
Section: Transition Metal Doping In Znocontrasting
confidence: 59%
“…Later, RTFM was also observed by Zhao et al 138 in Ni-, 2.25 atom %, doped ZnO thin film deposited by magnetron co-sputtering on a quartz substrate having the highest saturation magnetization of 0.055 μ B /Ni. However, an experimentally observed magnetic moment of Ni-doped ZnO was very less than the theoretical value calculated by Xue et al 139 which shows a magnetic moment of 0.79 μ B for a supper cell, which contains 32 Zn and 32 O atoms and containing a single Ni atom. In another work, He et al 140 found that electrical conductivity of ZnO increased 30 times on Ni doping, a higher oxidation state than Zn 2+ , with a decrease in resistivity from 390 to 12 ohm cm which is attributed to the Ni 3+ oxidation state which contributes to the hole carrier.…”
Section: Transition Metal Doping In Znocontrasting
confidence: 59%
“…In such cases, ZnO can be doped with a nickel compound, to enhance its intrinsic nature and developing its biosensing properties. Since, nickel and ZnO share similar ionic sizes, this Ni doped ZnO complex matrix becomes a promising biosensing tool [199].…”
Section: Biosensers Applied To Treatment Of Meningitismentioning
confidence: 99%
“…The Monkhorst–Pack scheme K-points mesh was set as 4 × 4 × 2 [ 37 ]. The structure optimization was performed until the residual force was less than 0.01 eV/Å on every atom [ 38 ]. In the process of calculating the band structure, the special points are X→R→M→Г→R (1 × 1 × 1 and 2 × 2 × 2 supercell) and Г→F→Q→Z→Г (2 × 2 × 3 supercell).…”
Section: Calculation Detailsmentioning
confidence: 99%